KUALITAS PELAYANAN KEPOLISIAN RESOR TEGAL DALAM PENANGANAN TAWURAN PELAJAR DI KABUPATEN TEGAL - Prasetiyo Aripin, Aditiya; Larasati Setianingsih, Endang; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Student brawls are a serious issue for the community in Tegal Regency. One of the strategies to address the issue of brawls is through the intervention of law enforcement agencies, specifically the Tegal Police Department. However, the services provided by the Tegal Police in handling student brawls still face several issues, including the high number of brawl cases in Tegal Regency. In this regard, some facts on the ground are still at odds with Article 2 of Law No. 2 of 2002 on the Indonesian National Police, which states that the police function as part of the state's governance in maintaining public security and order, enforcing the law, providing protection, guidance, and services to the public. This study analyzes the quality of service provided by the Tegal Police Department, particularly in handling student brawls, using conclusions from service quality theories by Zeithaml, Pasaruman, Berry, Moenir, and Pasolong with a descriptive qualitative approach. Data collection techniques include observation, documentation, and interviews. The results show that the service quality of the Tegal Police Department is still not optimal in the dimensions of tangibility, reliability, and the factors of ability and skill. This situation is influenced by several factors, such as inadequate facilities, the quality and quantity of human resources, and limited accessibility. The researcher provides recommendations to address the issues analyzed, including improving the underperforming dimensions. Actions that can be taken include gradually replacing old operational vehicles, enhancing personnel skills with realistic simulations, and improving infrastructure in remote areas to facilitate access.